A practical guide to shift-share instruments - Kirill Borusyak; Peter Hull; Xavier Jaravel (Centre for Microdata Methods and Practice (cemmap), 2024)
A recent econometric literature shows two distinct paths for identification with shift-share instruments, leveraging either many exogenous shifts or exogenous shares. We present the core logic of both paths and practical takeaways via simple checklists. A variety of empirical settings illustrate key points.
Keywords: 330; Shift-Share-Analyse; Ökonometrie; IV-Schätzung